Pendampingan pada peternak kambing dalam meningkatkan penghasilan keluarga di desa hutan dayurejo - Yustinus Budi Hermanto; Matheus Nugroho; Lasman Parulian Purba (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
This Community Service Activity (PKM) has partners who are a group of goat breeders located in the Dayurejo Forest Village on the slopes of Mount Arjuno, Prigen District, Pasuruan Regency, East Java. Of the 14 problems faced by partners, cultivating a cage and five goats worth giving to the community is the main priority that has been mutually agreed to be carried out on an area of ​​approximately 14 m2. The purpose of doing community service by supporting goat breeders is to provide a view that in the future if it is carried out diligently, the welfare of the breeder will be achieved slowly but tends to be more certain. The presence of five goats supported by the Abdimas Team is a form of implementing community service after implementing ANSOS with partners with the aim of supporting the forest economy in the future, including for families of farmers.